An uncommon cause of pneumonia: The golden diagnosis. (2017) - Fabbri, Laura; Tonelli, Roberto; Andreani, Alessandro; Castaniere, Ivana; Fantini, Riccardo; Marchioni, Alessandro; Clini, Enrico M.
Abstract: A 28-year-old sub-Saharan African Italian non-smoker male presented with signs and symptoms of pneumonia and respiratory failure. Despite antibiotic treatment he experienced a significant worsening of respiratory conditions and admission to intensive care unit. He thus underwent chest computed tomography followed by fiberopict bronchoscopy with bronchoalveolar lavage whose macroscopic examination led to the diagnosis of acute chest syndrome. A brief literature review was conducted to discuss the first manifestation of this disease.